2018
DOI: 10.1093/aob/mcy012
|View full text |Cite
|
Sign up to set email alerts
|

Scots pine aminopropyltransferases shed new light on evolution of the polyamine biosynthesis pathway in seed plants

Abstract: Contrary to previous views, our results demonstrate that SPMS activity is not a novel feature developed solely in the angiosperm lineage of seed plants but also exists as a secondary property in the Scots pine SPDS enzyme. The discovery of bifunctional SPDS from an evolutionarily old conifer reveals the missing link in the evolution of the polyamine biosynthesis pathway. The finding emphasizes the importance of pre-existing secondary functions in the evolution of new enzyme activities via gene duplication. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 71 publications
6
30
0
Order By: Relevance
“…We hypothesized that the enzymes in the PA metabolic pathway have acquired different functions during their evolution after the divergence of the seed plant lineages. This hypothesis was supported by our previous findings showing that the Scots pine has a bifunctional SPDS also possessing SPMS activity, which is contrary to angiosperms, which rely on separate enzymes in Spd and Spm biosynthesis (Vuosku et al, 2018). In the present study we are looking for other specific functional characteristics possibly existing in the PA metabolism of Scots pine.…”
Section: Introductionsupporting
confidence: 69%
See 4 more Smart Citations
“…We hypothesized that the enzymes in the PA metabolic pathway have acquired different functions during their evolution after the divergence of the seed plant lineages. This hypothesis was supported by our previous findings showing that the Scots pine has a bifunctional SPDS also possessing SPMS activity, which is contrary to angiosperms, which rely on separate enzymes in Spd and Spm biosynthesis (Vuosku et al, 2018). In the present study we are looking for other specific functional characteristics possibly existing in the PA metabolism of Scots pine.…”
Section: Introductionsupporting
confidence: 69%
“…PA biosynthetic knock-out mutants have indicated that ADC (Urano et al, 2005), SPDS (Imai et al, 2004) and SAMDC (Ge et al, 2006) are essential for embryo development in Arabidopsis (Arabidopsis thaliana L.). Both ADC and SPDS expressed in the mitotic cells of Scots pine zygotic embryos, which supports the essential roles of Put and Spd in basic cell functions (Vuosku et al, 2006;Vuosku et al,2018). In contrast, the Arabidopsis acl5-1 spms-1 double mutant, which contains neither Spm nor T-Spm, is viable and shows no phenotypic change except for the reduced stem growth due to acl5-1 (Imai et al, 2004).…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations